On the Self-Structuring Antenna - Katarzyna Jagodzińska (Sensors, 2020)
This paper shows the results of an investigation on the self-structuring antenna. This antenna consists of a combination of planar paths interconnected by controllable switches. A numerical electromagnetics code (NEC) environment and application with implemented genetic algorithms were used in this research. As a result of the investigation, an antenna template was built and measured.